PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2009-2012) - Tegar Rahardi; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of corporate governance on earnings management. Independent variables used in this study is the proportion of independent board, audit committee, the structure of managerial ownership and institutional ownership structure. In this study the proportion of independent board was measured by the percentage of the number of independent board of the entire board of commissioners in the company. Audit committee in this study was measured by adding up the audit committee in the company. Managerial ownership structure is measured by the percentage of shares owned by managers of the total shares outstanding. Institutional ownership structure is measured by the percentage of shares owned by the institutions of the total shares outstanding. Earnings management as the dependent variable proxied by discretionary accruals and is calculated by the modified Jones model. This study was conducted using data from documentation using www.idx.co.id, Indonesian Capital Market Directory (ICMD). The method of analysis used in this study is multiple linear regression. This study used a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) 2009-2012. The results showed simultaneous variable proportion of independent board, audit committee, the structure of managerial ownership and institutional ownership structure have a significant effect on earnings management. However, only partial audit committee variable, managerial ownership structure and institutional ownership structures are a significant effect on earnings management.